The effect of baby solus per Aqua (Baby spa) to sensory skill, fine motor skill and gross motor skill in children aged 6-24 months di Wawa Holistic Care Mojokerto - lida khalimatus sadiya; Tria Wahyuningrum; Lutfi Wahyuni; Yunika Nurtyas (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2020)
Background: Supporting of baby growth must be done in a comprehensive and quality manner that can be done through stimulation activities. Stimulation that is easily given actively to infants can be through tactile stimulation in the form of massages. Massage therapy can be combined with water therapy, which is a baby spa. Baby spas can be used to support the success of sensory skills, fine motor skills and gross motor skills.Objective: The study was to determine the effectiveness of Baby Spa on sensory skills, fine motor skills and gross motor skills in children aged 6-24 months.Method: The design used in this study was a pre-experimental design with a two-group pre-post-test approach. The variables in this study are the baby spa, sensory skills, fine motor skills and gross motor skills. Respondents were children aged 6 to 24 months totaling 29 children for the treatment group and 29 children for the control group. The treatment group will be treated eight times (2 times baby spa and six times massage). Previously conducted a pre-test, then after eight treatments carried out a post-test with an observation of sensory skills, fine motor skills and gross motor skills — data analysis using the Mann-Whitney test.Results: The results of data analysis on the sensory skill obtained p-value = 0.962 indicates that the baby spa is less effective against increasing sensory skills, while the fine motor skill p-value = 0,000 and gross motor skill obtained p-value = 0,000 means that the baby spa is effective against increasing fine motor skills and gross motor skills in children aged 6 to 24 months.Conclusion: That the Baby Spa is very effective against increasing fine motor skills and gross motor skills but the sensory skills are less effective. So you need sensory skill stimulation with baby spas and other methods.